Differential scanning calorimetry of native silk feedstock - Holland, C; Hawkins, N; Frydrych, M; Laity, P; Porter, D; Vollrath, F (Wiley, 2018)
Native silk proteins, extracted directly from the silk gland prior to spinning, offer access to a naturally hydrated protein that has undergone little to no processing. Combined with differential scanning calorimetry (DSC), it is possible to probe the thermal stability and hydration status of silk and thus investigate its denaturation and solidification, echoing that of the natural spinning process. It is found that native silk is stable between −10 °C and 55 °C, and both the high‐temperature enthalpy of denaturation (measured via modulated temperature DSC) and a newly reported low‐temperature ice‐melting transition may serve as useful quality indicators in the future for artificial silks. Finally, compared to albumin, silk's denaturation enthalpy is much lower than expected, which is interpreted within a recently proposed entropic desolvation framework which can serve to unveil the low‐energy aquamelt processing pathway.